Pengembangan Produk Minuman Fungsional Kombinasi Teh Hijau, Kopi Hijau dan Kayu Manis bagi Hiperkolesterolemia: Pengembangan Produk Minuman Fungsional Kombinasi Teh Hijau, Kopi Hijau, dan Kayu Manis bagi Hiperkolesterolemia - Harfika, Aviani; Hardinsyah, Hardinsyah; Rahman, Listhia Hardiati (Universitas Airlangga, 2023)
Background: Green tea, green coffee, and cinnamon are high in antioxidants and can improve blood lipid profiles. Objectives: The purpose of this study was to develop functional beverages consisting of green tea, green coffee, and cinnamon for people with hypercholesterolemia. Methods: This study was purely experimental with a completely randomized design. Three formulas of the functional beverages were: F1 (50% : 25% : 25%), F2 (40% : 35% : 25%), and F3 (35% : 40% : 25%). This study used organoleptic tests with 30 semi-trained panelists. The research data were analyzed using the Kruskal-Wallis H test. Results: The results of the hedonic test showed that there were no significant differences in the average color, flavor, aroma, viscosity, or after-taste characteristics (p>0.05). The panelist's most preferred formula was F2, with the highest acceptance for all test characteristics. The results showed that one serving of F2 beverage (100 mL) contained 1.1 g carbohydrates, 3.7 g protein, 0.7 g fat, and 304 mg AEAC/100 g antioxidants. Conclusions: The development of functional beverages consisting of green tea, green coffee, and cinnamon has the potential to be an alternative high-antioxidant beverage for hypercholesterolemia.